A case of multiple bile duct adenomas (biliary papillomatosis) with partial malignancy - OHARA, Hirotaka; KAMIYA, Yasutaka; MIYAJI, Makoto; OKAYAMA, Yasutaka; MATUBA, Shuzo; TAKEUCHI, Toshihiko; HAYASHI, Kotarou; SHIRAKI, Sigehiro; GOTO, Kazuo; NOGUTI, Yoshiki (Tando, 1988)
A 64-year-old woman was admitted to our hospital complaining of general fatigue and weight-loss. Ultrasonography (US) and computed tomography (CT) demonstrated multiple papillary tumors in the highly delated intrahepatic bile duct. Endoscopic retrograde cholangiopancreatography (ERCP) with a balloon catheter was performed demonstrating a normal pancreatic duct but a delated intra- and extra bile duct. In addition a right hepatic duct was obstructed with tumors and multiple filling defects were seen in a left hepatic duct. US guided percutaneous transhepatic cholangiography (PTC) and aspiration cytology of right intrahepatic bile duct and tumors were carried out, and the diagnosis was classified into group 5. Therefore we thought a radical surgery was not applicable. The patient died of jaundice with cholangitis and hemorrage after 15 months. By autopsy it was proved to be multiple bile duct adenomas in both the left and right hepatic bile duct. And a papillo-tubular adenocarcinoma was present in the minimum part of the adenomas.